2017
DOI: 10.1021/jacs.7b08628
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of Air-Stable Alloyed CsSn1–xPbxI3 Perovskite Nanocrystals for Use in Solar Cells

Abstract: Organic-inorganic hybrid perovskite solar cells have demonstrated unprecedented high power conversion efficiencies in the past few years. Now, the universal instability of the perovskites has become the main barrier for this kind of solar cells to realize commercialization. This situation can be even worse for those tin-based perovskites, especially for CsSnI, because upon exposure to ambient atmosphere the desired black orthorhombic phase CsSnI would promptly lose single crystallinity and degrade to the inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
275
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(286 citation statements)
references
References 91 publications
8
275
0
3
Order By: Relevance
“…Distinctively, several research groups demonstrated that Sn‐Pb binary perovskites could achieve better material stability in comparison with pure Sn‐based perovskites and even pure Pb‐based perovskites . Encapsulated Sn‐rich perovskite PDs (MA 0.975 Rb 0.025 Sn 0.65 Pb 0.35 I 3 ) could remain the photocurrent and dark current density over 200‐day storage . There results highlight that Sn‐Pb binary perovskites might have superb material stability.…”
Section: Challenges Of Sn‐pb Binary Perovskitesmentioning
confidence: 97%
“…Distinctively, several research groups demonstrated that Sn‐Pb binary perovskites could achieve better material stability in comparison with pure Sn‐based perovskites and even pure Pb‐based perovskites . Encapsulated Sn‐rich perovskite PDs (MA 0.975 Rb 0.025 Sn 0.65 Pb 0.35 I 3 ) could remain the photocurrent and dark current density over 200‐day storage . There results highlight that Sn‐Pb binary perovskites might have superb material stability.…”
Section: Challenges Of Sn‐pb Binary Perovskitesmentioning
confidence: 97%
“…A study of alloyed ASn 1− x Pb x I 3 (A = Cs + , FA + , MA + or their combinations) produced in the form of NCs showed the mixed compounds to be much more stable to ambient air as compared to both ASnI 3 and APbI 3 individually [9597]. The cation-exchange approach applied to produce FASn 1− x Pb x I 3 and FAPbI 3 from FASnI 3 is expected to be a general one and appropriate for the introduction of other isovalent and aliovalent cations such as Mn 2+ , Co 2+ , Bi 3+ , and Al 3+ into the sites of Sn 2+ or Pb 2+ [97].…”
Section: Reviewmentioning
confidence: 99%
“…In this regard, we speculated that modification of B site metal cations may also be effective to improve further optoelectronic properties of hybrid perovskites as the elements at B site directly affect the band‐energy structure of perovskites . Although, the pioneering work on compositional engineering at B site has been done by Hayase group based on Pb‐Sn binary system, the studies regarding B site engineering is still scarcer than mixed compositions at A site because the candidates for B site cations such as Sn are extremely unstable in air by oxidization . Interestingly, addition of germanium (Ge) at B site cation has been recently reported to be effective for the improvement of both stability and PCE of all‐inorganic perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%